2021
DOI: 10.17016/feds.2021.008
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Shock and Consumer Credit: Evidence from Credit Card Data

Abstract: We use credit card data from the Federal Reserve Board's FR Y-14M reports to study the impact of the COVID-19 shock on the use and availability of consumer credit across borrower types from March through August 2020. We document an initial sharp decrease in credit card transactions and outstanding balances in March and April. While spending starts to recover by May, especially for risky borrowers, balances remain depressed overall. We find a strong negative impact of local pandemic severity on credit use, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…This, however, comes at a cost (interest), and can in itself be taken as a measure of financial vulnerability. And even if some families do take out loans to afford housing expenses (Andersen et al 2020), Horvath et al (2020 shows that in the United States, since the onset of COVID-19, new supply of credit to risky borrowers is limited. In the presence of liquidity constrains, another important resource to consider are loans or gifts from family and friends, which can, likewise, ensure minimum levels of consumption.…”
Section: Related Literaturementioning
confidence: 99%
“…This, however, comes at a cost (interest), and can in itself be taken as a measure of financial vulnerability. And even if some families do take out loans to afford housing expenses (Andersen et al 2020), Horvath et al (2020 shows that in the United States, since the onset of COVID-19, new supply of credit to risky borrowers is limited. In the presence of liquidity constrains, another important resource to consider are loans or gifts from family and friends, which can, likewise, ensure minimum levels of consumption.…”
Section: Related Literaturementioning
confidence: 99%
“…Our paper contributes to the literature on the economic consequences of the COVID-19 pandemic. Previous studies have found that the pandemic strongly affects labor markets ( Coibion et al, 2020b ), stock markets ( Baker et al, 2020a , Fahlenbrach et al, 2020 ), consumer credit ( Horvath et al, 2021 ), household consumption ( Baker et al, 2020b ; Coibion et al, 2020a ), and overall economic activity ( Ludvigson et al, 2020 ). Concerning credit markets, there is evidence that large firms rapidly drew on their existing lines of credit at the beginning of the pandemic because of precautionary motives ( Acharya and Steffen, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“… Eichenbaum et al (2021) show that the policy interventions in response to the COVID-19 pandemic deepen the economic recession as they reduce consumption and labor supply. Empirical research provides evidence for a significantly negative impact of restrictive interventions on economic activity ( Carletti et al, 2020 ; Coibion et al, 2020a ; Kong and Prinz, 2020 ; Horvath et al, 2021 ). Coibion et al (2020a) show that restrictive policy interventions have a negative effect on real economic activity and household spending.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The credit scoring model is leveraged under credit policies, which is chanced depending on challenge environments. For example, during the COVID-19 pandemic that directly affects the applicants' creditworthiness [2], lenders will maintain the dept to prevent more increasing current NPLs. Besides, many situations affect the applicants' creditworthiness, such as economic conditions, financial crisis, and political situations.…”
Section: Introductionmentioning
confidence: 99%